FINANCIAL MANAGEMENT PRACTICES AND SUSTAINABILITY OF MSMEs IN UZBEKISTAN:A STUCTURED NARRATIVE REVIEW (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The sustainability of MSMEs during economic transition is influenced by their ability to manage finances effectively, including preparing budgets, managing capital, obtaining funding, and utilizing financial technology. Many studies on this topic have been conducted globally. However, comprehensive studies on financial management and its relationship to the sustainability of MSMEs in post-Soviet countries, particularly Uzbekistan, remain very limited. Using the Dynamic Capability Theory (DCT) framework, this paper highlights three key financial management practices that influence MSME sustainability: improving operational efficiency, strengthening financial stability, and fostering strategic adaptability. This article uses a structured narrative review approach, drawing on literature from 2019 to 2025, and a contextual analysis based on secondary data from the IMF, ADB, OECD, and World Bank. The analysis results show that in Uzbekistan, the ability to manage finance can have an impact that is stronger than in countries with more stable economies. The contribution of this research is an integrated conceptual framework comprising five aspects: a three-track sustainability-based DCT model and guidance for policy stages for further empirical research